Recombinant Antibodies to Face SARS-CoV-2 Syndemic: RAb to Face SARS-CoV-2 Syndemic - González Torres, Maykel; Leyva Gómez, Gerardo; Del Prado-Audelo, María Luisa; Cortés, Hernán; J. Magaña, Jonathan (Cellular and Molecular Biology, 2023)
In recent years, increasing interest has been paid to using antibody-based therapies for clinical applications. However, it is unclear whether recombinant antibodies can be combined with other scientific approaches to generate innovative solutions for mitigating severe acute respiratory syndrome coronavirus 2. In this context, the increase in this virus transmission, the number of infected people, and the interaction between social and biological processes have led to a syndemic, exacerbating the public health problem. Here, we argue about recent advances in recombinant antibody strategies and the perspective of using them to face this syndemic. Thus, the most promising methods in sample readiness, potency, and reduction of manufacturing time frame have been highlighted.